IT Support Challenges in Efforts to Increase Effectiveness and Efficiency in Manufacturing Companies - et. al., Aminudin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information technology has changed the perspective of business actors, both small and large scale businesses. Most business actors have used information technology for various things, from making PO, receiving goods, planning production, production processes, sending finished goods to customers, making invoices, tax invoices and others. To support optimal computerization, adequate infrastructure is needed, starting from hardware / software, computer networks, telecommunications networks and others. Information technology infrastructure must be properly maintained and maintained so as not to experience interference during use. One part that plays an important role in maintaining information technology is IT Support. IT Support is under the IT department and is responsible for the smooth running of all devices, both hardware and software. It is undeniable that information technology is developing rapidly and this is a challenge for an IT Support. Therefore, IT Support must have technical and non-technical capabilities in order to keep up with the constantly evolving technology so that it can work effectively and efficiently. IT Support skills need to be improved starting from hardware / software maintenance, computer network installation and trouble shooting, server and client computer installation, internet / cyber security, preventive and predictive maintenance, CCTV maintenance, hardware service / repair, ISO knowledge, graphic design and maintenance PABX.